Revisiting sacred metaphors: a religious studies pedagogical response to the rise of the nones - Shoemaker, Terry (The journal of religion & society, 2014)
The emergence of the religious nones can create pedagogical challenges due to the multifarious and institutionally disaffiliated nature of this classification. Thus, this article supplies a potential pedagogical technique by revisiting Peter Berger's sacred canopy metaphor. We submit that the religious nones can be understood functionally and structurally by employing "sacred metaphors" based on the sacred canopy. Three metaphors are provided herein to address the three central categories of the nones: unaffiliated believers, agnostics, and atheists. We introduce these sacred metaphors, detail their relevance, and suggest that these "sacred metaphors" present a new way of explaining the complexities of classifying the religious nones.